2004
DOI: 10.1210/me.2003-0498
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt Antagonist Secreted Frizzled-Related Protein-1 Is a Negative Regulator of Trabecular Bone Formation in Adult Mice

Abstract: Previous studies have associated activation of canonical Wnt signaling in osteoblasts with elevated bone formation. Here we report that deletion of the murine Wnt antagonist, secreted frizzled-related protein (sFRP)-1, prolongs and enhances trabecular bone accrual in adult animals. sFRP-1 mRNA was expressed in bones and other tissues of +/+ mice but was not observed in -/- animals. Despite its broad tissue distribution, ablation of sFRP-1 did not affect blood and urine chemistries, most nonskeletal organs, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
378
3
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 422 publications
(415 citation statements)
references
References 42 publications
22
378
3
1
Order By: Relevance
“…(18,19) Despite this controversy, there is in vivo evidence for a negative regulation of bone formation by Wnt antagonists such as DKK1, Krm2, or Sfrp1. (20)(21)(22)(23) These observations supported the existence of an in vivo cell autonomous effect of Wnts in osteoblasts. The role of Wnt signaling in controlling preosteoblastic cell proliferation and differentiation is not clear.…”
Section: Introductionsupporting
confidence: 69%
“…(18,19) Despite this controversy, there is in vivo evidence for a negative regulation of bone formation by Wnt antagonists such as DKK1, Krm2, or Sfrp1. (20)(21)(22)(23) These observations supported the existence of an in vivo cell autonomous effect of Wnts in osteoblasts. The role of Wnt signaling in controlling preosteoblastic cell proliferation and differentiation is not clear.…”
Section: Introductionsupporting
confidence: 69%
“…Alteration of several intracellular and extracellular controllers of the levels of transduced Wnt/b-catenin signaling has indeed been linked to disturbed skeletal homeostasis. (30)(31)(32)(33)(34) Using murine conditional genetic models, we and others have shown that Apc is involved in the regulation of both prenatal and postnatal bone mass accrual by regulating the levels of Wnt/b-catenin signalling. (11,12) This study confirms findings from these in vivo animal studies by demonstrating that heterozygous mutations in the APC gene are associated with a higher than normal bone mass in a majority of FAP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the removal of a Wnt inhibitor, the mouse knockout for Sfrp1 −/− displays an increase in trabecular bone mass in adult animals [22]. Previously identified as a BMP antagonist, SOST also binds to LRP5 and LRP6 in the extracellular region and antagonizes Wnt signaling [23,24].…”
Section: Introductionmentioning
confidence: 86%